266 Contact-free Snoring Solution Reduces Objectively-measured Snoring and Improves Bed Partners' Objectively-measured Sleep. (3rd May 2021) - Danoff-Burg, Sharon; Rus, Holly; Weaver, Morgan; Rodriguez, Rodolfo; Raymann, Roy
Abstract: Introduction: Snoring can disturb the sleep of snorers as well as their bed partners. Recent technological advances allow objective measurement of sleep and snoring in the comfort of the bedroom. This study examined effects of a non-medical contactless snoring solution on snoring and sleep in snorers and their partners. Methods: Self-reported snorers (n=29; 72% male; age 25-59 years, avg. 43; BMI<30) with non-snoring bed partners tracked their snoring nightly with the Do I Snore or Grind app while using the snoring solution at home (527 total nights across participants). During this time, partners tracked their own sleep nightly using ResMed S+. In addition, self-report data were collected from both snorers and partners. A within-subjects, pre-post design was used, comparing a 2-week baseline period to 2 weeks of nightly product use. Multilevel regression and paired t-tests were used to test for statistical significance. The snoring solution (Smart Nora) included a pillow insert that gently inflates when early sounds of snoring are detected, enabling breathing to return to normal. Results: Objectively-measured average snoring reduced from 10% of the night when not using the product to 9% during the first week of use and 7% during the second week of use (p<.05). Partners perceived the snoring as less loud and less severe when the product was used. At the end of the study, no partner described the snoring as severe. Objectively-measured sleep of partners revealed a 16% decrease in wake after sleep onset (p<.05). Prior to product use, they spent an average of 38 minutes awake after falling asleep (approximately 9% of their sleep period). This decreased to 34 minutes during the first week of product use and to 32 minutes during the second week. Product use also led to improvements in the perceived sleep of snorers and their partners, including ability to sleep through the night without waking up, overall sleep quality, and feeling rested upon waking in the morning (all ps<.05). Conclusion: By reducing the amount of snoring, the contactless snoring solution improved objectively-measured sleep in snorers' bed partners. Also, the perceived sleep of both snorers and their partners improved. Support (if any): Smart Nora